2016
DOI: 10.1177/1471301216682118
|View full text |Cite
|
Sign up to set email alerts
|

Public attitudes towards people living with dementia: A cross-sectional study in urban Japan (innovative practice)

Abstract: Stigma and social isolation are major challenges in building dementia friendly communities. Information is a key factor in improving knowledge and attitudes about dementia. This cross-sectional survey aimed to investigate public attitudes towards people with dementia in an urban community in Japan. Nearly 90% of the participants responded that they were able to have a good relationship with a person with dementia and help such a person if needed. However, around half of the participants would be ashamed of a f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
32
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(39 citation statements)
references
References 12 publications
6
32
0
1
Order By: Relevance
“…Nearly half of the participants in a Japanese study report being ashamed of a family member being diagnosed with dementia. [30] Poor mental health literacy among the public regarding dementia juxtaposed with negative public attitude serves as a major deterrent to seek timely help from a medical professional[31], which can ultimately lead to more severe adverse outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Nearly half of the participants in a Japanese study report being ashamed of a family member being diagnosed with dementia. [30] Poor mental health literacy among the public regarding dementia juxtaposed with negative public attitude serves as a major deterrent to seek timely help from a medical professional[31], which can ultimately lead to more severe adverse outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Currently, most previous studies on dementia literacy have been conducted in developed countries, such as Australia, 3 the United States, 6 and Japan. 10 Thus, a knowledge gap exists in the dementia literacy of citizens in LMICs. Understanding dementia literacy in the Western Pacific Region is the essential first step in designing an effective public health approach in the region.…”
Section: Introductionmentioning
confidence: 99%
“…Several other characteristics of Japanese culture could also interfere with making visits to a memory clinic. Around half of respondents in previous research indicated that they would be ashamed of having a family member with dementia . In efforts to encourage help‐seeking behaviour, we developed the JOSS as a brief screening tool that used familiar folktales to detect cognitive disease, making the test more enjoyable, like a game, and thus less threatening.…”
Section: Discussionmentioning
confidence: 99%
“…Around half of respondents in previous research indicated that they would be ashamed of having a family member with dementia. 18 In efforts to encourage help-seeking behaviour, we developed the JOSS as a brief screening tool that used familiar folktales to detect cognitive disease, making the test more enjoyable, like a game, and thus less threatening. We believe that the ease with which potential patients with cognitive disease accepted the JOSS's format and content makes this scale a useful cognitive screening examination that could help make the referral step easier and a visit to a memory clinic less threatening.…”
Section: Discussionmentioning
confidence: 99%